Assistance in Prayer Practices for Dyslexic Students at the Integrated Islamic Junior High School Permata Probolinggo - Shodiqoh, Hanifah Nurul; Khadavi, M. Jadid (FALASIFA : Jurnal Studi Keislaman, 2025)
This research aims to analyze the process of accompanying prayer practices for dyslexic students at Islamic Junior high school Permata at Probolinggo City. Dyslexia, as a learning disorder that affects reading and writing abilities, often presents additional challenges in carrying out religious practices, including prayer. This research employs a qualitative approach with data collection through observation, interviews, and documentation of the mentoring program implementation. The results show that the implemented mentoring program successfully improved the understanding and skills of dyslexic students in performing prayers. Mentoring was conducted using dyslexia-friendly methods such as the use of visual materials, step-by-step instructions, and consistent emotional support. Students showed significant improvement in performing prayers independently and gained benefits in terms of self-confidence and spiritual involvement. This study concludes that mentoring strategies tailored to the needs of dyslexic students can enhance the quality of their worship. These findings recommend the implementation of similar approaches in other schools to support students with special needs and reinforce the importance of adapting teaching methods in the context of religious practices